The implementation of the Plan Esperanza and response to the imPACT Review. Issue 10 (October 2017) - Vidaurre, Tatiana; Santos, Carlos; Gómez, Henry; Sarria, Gustavo; Amorin, Edgar; López, Marga; Regalado, Roxana; Manrique, Javier; Tarco, Duniska; Ayestas, Carlos; Calderón, Mónica; Mas, Luis; et al.
Summary: Following the implementation of the National Cancer Prevention and Control Results-based Budget Programme (PpR Cancer–024) in 2011, the Peruvian Government approved the Plan Esperanza—a population-based national cancer control plan—in 2012. Legislation that ensured full government-supported funding for people who were otherwise unable to access or afford care and treatment accompanied the Plan. In 2013, the Ministry of Health requested an integrated mission of the Programme of Action for Cancer Therapy (imPACT) report to strengthen cancer control in Peru. The imPACT Review, which was executed in 2014, assessed Peru's achievements in cancer control, and areas for improvement, including cancer control planning, further development of population-based cancer registration, increased prevention, early diagnosis, treatment and palliative care, and the engagement and participation of civil society in the health-care system. This Series paper gives a brief history of the development of the Plan Esperanza, describes the innovative funding model that supports it, and summarises how funds are disseminated on the basis of disease, geography, and demographics. An overview of the imPACT Review, and the government's response in the context of the Plan Esperanza, is provided. The development and execution of the Plan Esperanza and the execution of and response to the imPACT Review demonstrates the Peruvian Government's commitment to fighting cancer across the country, including in remote and urban areas.